Analysis of Hospital Readmissions After Prosthetic Urologic Surgery in the United States: Nationally Representative Estimates of Causes, Costs, and Predictive Factors. Issue 8 (12th July 2017) - Pederzoli, Filippo; Chappidi, Meera R.; Collica, Sarah; Kates, Max; Joice, Gregory A.; Sopko, Nikolai A.; Montorsi, Francesco; Salonia, Andrea; Bivalacqua, Trinity J.
Abstract: Background: The surgical treatment of urinary incontinence and erectile dysfunction by prosthetic devices has become part of urologic practice, although sparse data exist at a national level on readmissions and hospital costs. Aim: To assess causes and costs of early (≤30 days) and late (31–90 days) readmissions after implantation of penile prostheses (PPs), artificial urinary sphincters (AUSs), or PP + AUS. Methods: Using the 2013 and 2014 US Nationwide Readmission Databases, sociodemographic characteristics, hospital costs, and causes of readmission were compared among PP, AUS and AUS + PP surgeries. Multivariable logistic regression models tested possible predictors of hospital readmission (early, late, and 90 days), increased hospital costs, and prolonged length of stay at initial hospitalization and readmission. Outcome: Outcomes were rates, causes, hospital costs, and predictive factors of early, late, and any 90-day readmissions. Results: Of 3, 620 patients, 2, 626 (73%) had PP implantation, 920 (25%) had AUS implantation, and 74 (2%) underwent PP + AUS placement. In patients undergoing PP, AUS, or PP + AUS placement, 30-day (6.3% vs 7.9% vs <15.0%, P = .5) and 90-day (11.6% vs 12.8% vs <15.0%, P = .8) readmission rates were comparable. Early readmissions were more frequently caused by wound complications compared with late readmissions (10.9% vs <4%, P = .03). Multivariable models identified longer length of stay, Charlson Comorbidity Index score higher than 0, complicated diabetes, and discharge not to home as predictors of 90-day readmissions. Notably, hospital volume was not a predictor of early, late, or any 90-day readmissions. However, within the subset of high-volume hospitals, each additional procedure was associated with increased risk of late (odds ratio = 1.06, 95% CI = 1.03–1.09, P < .001) and 90-day (odds ratio = 1.03 95% CI = 1.02–1.05, P < .001) readmissions. AUS and PP + AUS surgeries had higher initial hospitalization costs ( P < .001). A high hospital prosthetic volume decreased costs at initial hospitalization. Mechanical complications led to readmission of all patients receiving PP + AUS. Clinical Implications: High-volume hospitals showed a weaker association with increased initial hospitalization costs. Charlson Comorbidity Index, diabetes, and length of stay were predictors of 90-day readmission, showing that comorbidity status is important for surgical candidacy. Strengths and Limitations: This is the first study focusing on readmissions and costs after PP, AUS, and PP + AUS surgeries using a national database, which allows ascertainment of readmissions to hospitals that did not perform the initial surgery. Limitations are related to the limited geographic coverage of the database and lack of surgery- and surgeon-specific variables. Conclusions: Analysis of readmissions can provide better care for urologic prosthetic surgeries through better preoperative optimization, counseling, and resource allocation.